Meaningful Science Learning by the Use of an Additional Language: A Tanzanian Perspective. Issue 3 (2nd September 2019) - Mkimbili, Selina Thomas
Abstract : Science education today focuses on preparing future citizens who are critical consumers of scientific knowledge and not merely recipients of scientific facts. Thus, meaningful science learning is important in the learning process. The aim of this paper is to explore approaches for facilitating meaningful science learning in a context where an additional language is used as a language of instruction. The findings of this article were drawn from a video study of six teachers in classrooms in Tanzania and group interviews with 18 of their students. The findings suggest various approaches that can support dialogue by the use of an additional language. From this study it was noted that the home language of the learners can be utilised as a mediating agent to facilitate meaningful science learning using an additional language. In addition, hands-on activities, the use of gestures and real-life examples emerge as strategies supporting meaningful science learning in a multilingual context.